Immobilization of protease extracted from Bacillus sp. P45 on different supports - Reis, Daiane Felix; Fadanni, Odivane; Brandelli, Adriano; Kalil, Susana Juliano (VETOR - Revista de Ciências Exatas e Engenharias, 2020)
Immobilization is a direct tool which not only improves the activity and stability of enzymes, but also enables their reuse. Therefore, selecting methods and supports to obtain biocatalysts with high selectivity and thermal stability is an important step. This study aimed at evaluating the immobilization of partially purified protease from Bacillus sp. P45, by different methods with the use of the following carriers: Amberlite IR® 120, montmorillonite clay, chitosan, glutaraldehyde-activated chitosan, Eupergit® C, DEAE-Cellulose® and QAE-Sephadex®. It also aimed at determining the operational stability of the derivative. The best results were obtained with the use of glutaraldehyde-activated chitosan, Amberlite IR® 120 and montmorillonite clay, with loading capacities of 25.4, 6.2 and 2.3 U/g support, respectively. Regarding the operational stability of the derivative glutaraldehyde-activated chitosan, the enzyme was found to keep 53.5% of its residual activity after being reused four times.